(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2021)
Background: Pre-eclampsia is a major cause of maternal or fetal morbidity and mortality. Its pathophysiology is still an area of dilemma. Homocysteine is a sulfur containing amino acid, which damages smooth muscle of the vessel wall. The objective of this study was to investigate the association of serum homocysteine levels with preeclampsia. Materials and methods: This case control study was carried out in the Department of Obstetrics & Gynecology Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, from April 2017 to March 2018. The study reviewed a total of 108 women with pregnancy. These participants were categorized into three groups: healthy pregnant subjects group, mild preeclampsia group and severe preeclampsia group. The three study groups were statistically similar in aspects of maternal age, gestational age and parity. Results: The mean serum homocysteine level was found 16.4±7.9 μmol/l in mild preeclampsia group, 20.8±8.0 μmol/l in severe preeclampsia group and 8.2±3.7 μmol/l in the group of normal pregnant women. Serum homocysteine was significantly increased in severe preeclampsia and mild preeclampsia in comparison to normal group without preeclampsia. Significant positive correlation was found between systolic blood pressure (p=0.001) diastolic blood pressure (p=0.001) with serum homocysteine level. Conclusion: The study concluded that a significant positive association was found between pre-eclampsia and maternal serum homocysteine levels. This may provide informationonthe role of homocysteine in preeclampsia with a preventive strategy of consequences of this condition. JCMCTA 2021 ; 32 (1) : 14-20